Development of a Scaled Buoyant Baby-Cot for Emergency Flood-Aid - Nabil Qayyum Roslan; Miqdad Khairulmaini; Hasannuddin Abd Kadir; Ahmad Najmie Rusli (Journal of Advanced Mechanical Engineering Applications, 2026)
Malaysia is one of the regions in southeast Asia prone to monsoons. During this period, flooding often displaces communities. Most household furniture is not designed for emergency use. One furniture which has the potential to be used during emergencies is the baby cot. However, standard baby-cots are heavy and not buoyant, making them unsuitable for carrying items during flood evacuation. This study involves the design and fabrication of a buoyant baby-cot that can be used during normal and emergency situations. The prototype was designed using SolidWorks and built using PVC pipes and 5 mm acrylic sheets. The total cost for the prototype was RM303.10. Simulation using Finite Element Analysis (FEA) under 50 N showed a maximum displacement of 5.206 × 10?3 mm, indicating that the frame is structurally stable. When used in normal situations, testing showed that the prototype can support up to 10 kg, while when tested for flood situation, testing showed that the prototype can float while supporting loads up to 6 kg and remain watertight for more than 30 minutes. The results clearly show that the prototype is structurally stable and affordable, and it can be used as a simple emergency response solution during floods.